2007
DOI: 10.1088/1748-0221/2/04/p04004
|View full text |Cite
|
Sign up to set email alerts
|

Energy resolution of the barrel of the CMS Electromagnetic Calorimeter

Abstract: The energy resolution of the barrel part of the CMS Electromagnetic Calorimeter has been studied using electrons of 20 to 250 GeV in a test beam. The incident electron's energy was reconstructed by summing the energy measured in arrays of 3×3 or 5×5 channels. There was no significant amount of correlated noise observed within these arrays. For electrons incident at the centre of the studied 3×3 arrays of crystals, the mean stochastic term was measured to be 2.8% and the mean constant term to be 0.3%. The amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…To study the pulse shape and determine the intrinsic time resolution of the ECAL detector, electrons from a test beam are used. Several fully equipped barrel and endcap sectors were exposed to electrons at the H2 and H4 test beam facilities at CERN, prior to their installation into the CMS detector [3]. The beam lines delivered electrons with energies between 15 GeV and 250 GeV.…”
Section: Time Measurement Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the pulse shape and determine the intrinsic time resolution of the ECAL detector, electrons from a test beam are used. Several fully equipped barrel and endcap sectors were exposed to electrons at the H2 and H4 test beam facilities at CERN, prior to their installation into the CMS detector [3]. The beam lines delivered electrons with energies between 15 GeV and 250 GeV.…”
Section: Time Measurement Resolutionmentioning
confidence: 99%
“…In the barrel region, the target energy resolution for unconverted photons with energies larger than 50 GeV is 0.5%. Tests illuminating 25% of all ECAL barrel crystals with 120 GeV electrons have demonstrated that this target resolution is achievable [3]. Searches for the Higgs boson particularly benefit from this performance: a Standard Model Higgs with a mass of 120 GeV can be observed by CMS in the two-photon decay channel with a 5σ significance with less than 10 fb −1 of integrated luminosity collected at 14 TeV center of mass energy [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In the endcaps, the crystals are arranged instead in a rectangular (x, y) grid, with a front-face area of 2.9×2.9 cm 2 . The intrinsic energy resolution of the ECAL barrel was measured with an ECAL supermodule directly exposed to an electron beam, without any attempt to reproduce the material of the tracker in front of the ECAL [21]. The relative energy resolution is parameterized as a function of the electron energy as…”
Section: The Electromagnetic Calorimetermentioning
confidence: 99%
“…This spread can be quite small when electrons lose little energy via bremsstrahlung before reaching ECAL. For example, electrons of 120 GeV in a test beam that impinge directly on the centre of a crystal deposit about 97% of the energy in a 5×5 crystal array [24]. For an electron produced within CMS, the effect induced by radiation of photons can be large: on average, 33% of the electron energy is radiated before it reaches the ECAL where the intervening material is minimal (η ≈ 0), and about 86% of its energy is radiated where the intervening material is the largest (|η| ≈ 1.4).…”
Section: Clustering Of Electron Energy In the Ecalmentioning
confidence: 99%